Analisis Pengaruh Dosis Radiasi Eksternal Akumulasi Dosis yang Diterima Petugas Radiasi di Ruang Penyinaran Radioterapi RSUP dr.Hasan Sadikin Bandung - Budi Muhammad AR; Eko Hidayanto; Very Richardina (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
In radiation utilization, the regulation should be applied to minimize radiation dose received by the officer in order not to exceed the provision of Dose Limit Value based on BAPETEN Regulation No. 4 of 2013 that the average of equivalent dose is ≤50 mSv/year and ≤20 mSv for five-year period. The purpose of this study was to analyze the external radiation dose received by each officer at Radiotherapy Installation RSUP dr.Hasan Sadikin Bandung based on the NBD that has been determined. The equivalent dose values were obtained from the Thermoluminisence Dosemeter (TLD) of each officer over a five-year period from 2012 to 2016 that had been read by using a TLD reader. Then the radiation exposure measured by using a surveymeter with a distance of 3 meters from each teleterapi aircraft with radioactive sources to predict the distance factor between officers and radiation sources. The results showed that teleterapi operators received the highest equivalent dose in a five-year period with a dose value of 0.206 mSv/year, then in 2013 the external radiation dose received by officers and medical physicists reached the highest value when compared to another officers, with the average value of equivalent dose was 0.085 mSv/year and 0.55 μSv/hour. If observed from the distance factor, in 2013 each officer tends to come near to the source of radiation at every working hour. All radiotherapy officers at RSUP dr.Hasan Sadikin Bandung from 2012 to 2016 received a safe radiation dose and not exceed the NBD determined by BAPETEN. Keywords: Dose Limit Value, External Radiation Dose, Equivalent Dose, Distance